Estrategias climáticas de largo plazo en América Latina: qué podemos aprender desde la voz de los actores que han participado en su formulación? - Paulina Calfucoy; Marta Torres Gunfaus; Andreas Fazekas; Adrien Vogt-Schilb (Inter-American Development Bank (IDB), 2022)
– Long-term Strategies for Decarbonization, termed long-term low emissions and development strategies (LT-LEDS) by the UNFCCC, and sometimes referred to as LTS, can influence the transition to a resilient and decarbonized economy. LT-LEDS additionally make it possible to identify investments and regulatory changes needed to enable the deployment of new technologies and to identify measures which facilitate a just transition. This study seeks to improve the understanding of the value that LT-LEDS can bring to climate policy and action at the national level, based on the perspective of local actors who have participated in their design. The study explores the process of formulating LT-LEDS in Chile, Colombia, Costa Rica, and Peru. It combines three distinct methodologies, namely content analysis, literature review and semi- structured interviews with actors who participated in the LT-LEDS design processes. We identify common aspects among these processes, as well as weaknesses and difficulties, and provide recommendations for formulating and updating LT-LEDS. Stakeholders expressed their appreciation for many of the attributes of LT-LEDS, for instance using simulations to demonstrate how long-term goals can be achieved, and the possibility of using LT-LEDS to assess and inform Nationally Determined Contributions (NDCs). However, LT-LEDS are sometimes perceived as instruments primarily designed to fulfill external requirements but disconnected from national development priorities (and from the need to improve resilience). In addition, LT- LEDS are not yet fully equipped to mobilize the private sector. The findings of this study can be taken into consideration to improve LT-LEDS drafting processes.
Keywords: 330; climate strategies; decarbonization; climate governance; Paris agreement; climate policy